The enemy below [videorecording (DVD)] - Mitchum, Robert; Jürgens, Curd, 1915-1982; Hedison, David, 1929-2019-; Bikel, Theodore; Rayner, D. A. (Denys Arthur), 1908- (Fox war classics., 2004)
Set during the Battle of the Atlantic during World War II, the film tells the story of the cat and mouse hunt between the USS Haynes, a destroyer escort, and a German U-Boat. Captain Murrell, a former Merchant Mariner, saw his wife killed when his freighter was torpedoed by the Germans. Von Stolberg, the veteran U-Boat commander, sees no honor in the German aims of the war. Both of these highly experienced men must now try to outthink and outmaneuver each other, knowing that any mistake can bring instant defeat and death.